What Should We Do With People Who Cannot or Do Not Want to Be Protected From Neurotechnological Threats? - Inglese, Silvia; Lavazza, Andrea (Frontiers in Human Neuroscience, 2021)
Neurotechnologies can pose a threat to people's privacy and mental integrity. Hence the proposal of establishing neurorights (Ienca and Andorno, 2017) and technical principles for the implementation of these rights (Lavazza, 2018). However, concepts such as ‘the extended mind’ and what might be called ‘the post-human objection’ can be said to challenge this protection paradigm. On the one hand, it may be difficult to outline the cognitive boundaries between humans and machines (with the consequent ethical and legal implications). On the other hand, those who wish to make strong use of neurotechnologies, or even hybridize with them, reject the idea that privacy and mental integrity should be protected. However, from the latter view, issues may arise relating to the protection of persons entering into relationships with posthumanist people. This article will discuss these scenarios as well as the ethical, legal, social, and political issues that could follow from them.